A versatile multicomponent database for the surface tension of liquid metals. (June 2019) - Vermot des Roches, Mathieu; Gheribi, Aïmen E.; Chartrand, Patrice
Abstract: Experimental surface tension data for many binary, ternary and higher order metallic systems is unfortunately currently unavailable in the literature. This could be detrimental in several practical and industrial applications. Consequently, having a theoretical model with a good predictive capability is highly desirable. In general, the surface tension of metallic alloys is predicted via the well-established Butler model. This model assumes a linear relationship between the excess Gibbs energy in the Bulk and on the surface. For many systems, this assumption is not valid, especially for systems based on elements with different bulk electronic structures, for which the Butler model fails to predict the composition dependence of the surface tension (As demonstrated in this work, the Butler model is accurate only for about 65% of metallic system for which experimental data is available). The aim of this paper is to propose an alternative to the Butler model to represent accurately the surface tension multi component liquid metals. The proposed model is an extension of the Guggenheim model of ideal solutions to take into account the difference of electronic structures between elements of a solution. The model is compared with the 36 binary and 7 ternary metallic alloys for which experimental data is available. It is shown that the accuracy of the model is higher than 95%. On that basis, the composition dependence of the surface tension of many other binary alloys for which experimental data is not available is predicted. The extension of the model to ternary and higher order systems is proposed without introducing any new parameters, i.e. by considering only the binary parameters. It is shown that the extended model provides also an accurate prediction of the surface tension for ternary metal.